(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, a high-accuracy H^1-Galerkin mixed finite element method (MFEM) for strongly damped wave equation is studied by linear triangular finite element. By constructing a suitable extrapolation scheme, the convergence rates can be improved from O(h) to O(h^3) both for the original variable u in H^1(Ω) norm and for the actual stress variable P=∇u_t in H(div;Ω) norm, respectively. Finally, numerical results are presented to confirm the validity of the theoretical analysis and excellent performance of the proposed method.